2019
DOI: 10.1039/c9nr03353j
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional biomimetic nanoparticles loading baicalin for polarizing tumor-associated macrophages

Abstract: Immunosuppression and immune tolerance lead tumor cells to evade immune system surveillance and weaken drug efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…Several studies have demonstrated that nanodrugs offer superiority in mediating the polarization of macrophages with increased drug uptake. For instance, curcumin (cur), baicalin (Bai), and ginseng-derived nanoparticles have been reported to alter TaM polarization without discernible toxicity (90)(91)(92). compared to the drugs themselves, their nanoparticle derivatives showed improved pharmacokinetics and bioavailability in systemic circulation, and thus contributed toward excellent antitumor responses (90)(91)(92).…”
Section: Tam-targeted Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that nanodrugs offer superiority in mediating the polarization of macrophages with increased drug uptake. For instance, curcumin (cur), baicalin (Bai), and ginseng-derived nanoparticles have been reported to alter TaM polarization without discernible toxicity (90)(91)(92). compared to the drugs themselves, their nanoparticle derivatives showed improved pharmacokinetics and bioavailability in systemic circulation, and thus contributed toward excellent antitumor responses (90)(91)(92).…”
Section: Tam-targeted Therapeuticsmentioning
confidence: 99%
“…For instance, curcumin (cur), baicalin (Bai), and ginseng-derived nanoparticles have been reported to alter TaM polarization without discernible toxicity (90)(91)(92). compared to the drugs themselves, their nanoparticle derivatives showed improved pharmacokinetics and bioavailability in systemic circulation, and thus contributed toward excellent antitumor responses (90)(91)(92). Furthermore, few materials used in nanoparticle production, including Tio 2 and ag, may preferentially polarize TaMs towards an M1 phenotype (93,94).…”
Section: Tam-targeted Therapeuticsmentioning
confidence: 99%
“…Their shift between the classically activated (M1, proinflammatory) and alternatively activated (M2, anti-inflammatory) phenotypes has been recognized as a crucial factor in the initiation, progression, and termination of numerous inflammatory diseases (Zhang et al, 2018) and especially in influenza virus infection (Halstead et al, 2018). Modulation of macrophage polarization has previously been shown to inhibit or promote influenza infection by applying GM-CSF (Sun et al, 2018) or Afatoxin B1 (Han et al, 2019), respectively. In this study, we confirm that the high mortality of infected mice is correlated with an abundant recruitment of macrophages to the lung and a high proportion of M1-polarized macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…NPs were further entrapped in a galactose-modified erythrocyte coating to increase biocompatibility and TAM targeting, the macrophage galactose-type lectin (MGL; CD301) receptor is expressed on myeloid antigen-presenting cells including macrophages. These biomimetic NPs also suppressed melanoma growth in vivo and increased the infiltration of CD8+ T cells into the TME [40].…”
Section: Reprogramming the Immunosuppressive Tme With Nanotherapeuticsmentioning
confidence: 93%